Feasibility of planned mini-laparotomy and adhesiolysis at the time of robotic-assisted radical prostatectomy in patients with prior major abdominal surgery - Rajih, Emad; Alhathal, Naif; Alenizi, Abdullah M.; El-Hakim, Assaad (Canadian Urological Association Journal, 2016)
Introduction: Our aim was to report our experience on the feasibility of completing radical prostatectomy robotically after planned open adhesiolysis for prior major abdominal surgery with previous midline laparotomy scar. Methods: We searched our prospectively collected database of robotic assisted-radical prostatectomy (RARP) performed between October 2006 and October 2012 by a single fellowship-trained surgeon to identify all patients who underwent planned initial minilaparotomy for release of abdominal adhesions at time of RARP. Among 250 RARP patients, five patients fulfilled these criteria. Results: All patients had prostatectomy completed robotically. The mean values of patients’ demographics were as follows: Age 61.8 years (range 54‒69), body mass index 30.7 (range 24.3‒5.3), and prostate volume 41.5 ml (range 30.8‒54). Mean operative time was 245 min (range 190‒280) and estimated blood loss 410 ml (range 300‒650). Median hospital stay was one day (range 1‒7). Postoperatively, there was one prolonged ileus, which resolved spontaneously, and one myocardial infarction. Conclusions: Robotic completion of radical prostatectomy after open adhesiolysis is feasible. This approach maintains most minimally invasive advantages of RARP, despite a slightly longer hospital stay. In the best interest of patients, robotic surgeons are encouraged to finish the case robotically rather than attempting an open approach.